Post-stroke dysphagia and ambient air pollution are associated with dementia - Lee, Kuo-Wei; Chung, Hao-Wei; Hsieh, Hui-Min; Tsao, Yu-Hsiang; Hung, Chih-Hsien; Feng, Ming-Chu; Hung, Chih-Hsing (Frontiers in Aging Neuroscience, 2023)
Introduction: This cohort study aimed to explore the potential association between ambient air pollution and dementia incidence in adults who have experienced a stroke. Additionally, the study aimed to determine dysphagia as a predictive factor for the subsequent development of dementia in patients with stroke. Materials and Methods: This retrospective nested case-control study used data from the Kaohsiung Medical University Hospital Database in Taiwan. Data collected include average ambient air pollution concentrations within 3 months and 1 year after the index dysphagia date. The primary outcome includes incident dementia in patients with or without dysphagia.Logistic regression analysis was performed to examine the association between significant air pollution exposure and the risk of dementia while controlling for baseline demographic characteristics (age and sex), and comorbidities. Results: The univariable regression models revealed a higher likelihood of dementia diagnosis in patients with dysphagia (odds ratio = 1.493, 95% confidence interval = 1.000-2.228). The raw odds ratios indicated a potential link between air pollution exposure and elevated dementia risks in the overall study population and patients with stroke without dysphagia, except for O3. Particulate matter (PM)2.5 and nitrogen oxide (NOx) exhibited significant effects on the risk of dementia in the stepwise logistic regression models.The presence of dysphagia following a stroke may pose a risk of developing dementia.